Gaya Bahasa Komentator Sepak Bola dalam Acara AFF U 18 di Stasiun Televisi Indosiar - Eka Setya Budi; Yushinta Eka Farida (Universitas Islam Nahdlatul Ulama Jepara, 2017)
This research aims to analyze language style used by commentators of soccer in AFF U 18 on the television station of Indosiar in an aspect of direct utterance. The research data is language style used by soccer commentators. The data sources of research is verbal language used by soccer commentators in AFF U18 on Indosiar television station. The collecting data used is technique of recording to record verbal language. This research used qualitative method with descriptive method. The research results show (1) language style used by soccer commentators in AFF U 18 on Indosiar television station with finding utterances are 3 language styles, they are climax, antithesis, and repetition, and (2) language style used based on direct or indirect the meanings found are 10 language styles, they are metaphora, personification, eponym, alliteration, assonance, hyperbole, erothesis, simile, and irony.